Solution to Equation

Algebra Level 3

x = x 1 x + 1 1 x \large x = \sqrt{x-\frac 1x} + \sqrt{1-\frac 1x}

Find the sum of all real values of x x satisfying the equation above.


The answer is 1.618.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

x = x 1 x + 1 1 x Multiply both sides by x x x = x 2 1 + x 1 = x 1 ( x + 1 + 1 ) Squaring both sides x 3 = ( x 1 ) ( x + 1 + 2 x + 1 + 1 ) x 3 = x 2 + x 2 + 2 ( x + 1 ) ( x 2 2 x + 1 ) x 3 x 2 x + 2 = 2 x 3 x 2 x + 1 Let u = x 3 x 2 x + 1 u 2 2 u + 1 = 0 ( u 1 ) 2 = 0 u = 1 x 3 x 2 x + 1 = 1 x 3 x 2 x + 1 = 1 x ( x 2 x 1 ) = 0 \begin{aligned} x & = \sqrt{x-\frac 1x} + \sqrt{1-\frac 1x} & \small \color{#3D99F6} \text{Multiply both sides by }\sqrt x \\ x\sqrt x & = \sqrt{x^2-1} + \sqrt{x-1} \\ & = \sqrt{x-1}\left(\sqrt{x+1}+1\right) & \small \color{#3D99F6} \text{Squaring both sides} \\ x^3 & = (x-1)\left(x+1+2\sqrt{x+1}+1\right) \\ x^3 & = x^2+x-2+2\sqrt{(x+1)(x^2-2x+1)} \\ x^3-x^2-x+2 & = 2\sqrt{x^3-x^2-x+1} & \small \color{#3D99F6} \text{Let }u = \sqrt{x^3-x^2-x+1} \\ \implies u^2 - 2u + 1 & = 0 \\ (u-1)^2 & = 0 \\ u & = 1 \\ \sqrt{x^3-x^2-x+1} & = 1 \\ x^3-x^2-x+1 & = 1 \\ x(x^2 - x-1) & = 0 \end{aligned}

{ x = 0 x = 1 + 5 2 x = 1 5 2 \implies \begin{cases} x = 0 \\ x = \dfrac {1+\sqrt 5}2 \\ x = \dfrac {1-\sqrt 5}2 \end{cases}

But only x = 1 + 5 2 = φ x = \dfrac {1+\sqrt 5}2 = \varphi , the golden ratio, satisfies the original equation. Therefore the sum of all real value of x x satisfying the equation is φ 1.618 \varphi \approx \boxed{1.618} .

Fantastic solution sir

Arka Dutta - 2 years, 2 months ago

Log in to reply

Glad that you like it.

Chew-Seong Cheong - 2 years, 2 months ago
Arka Dutta
Apr 5, 2019

Since (x-1/x)^1/2 and (1-1/x)^1/2 both are greater equal to 0 then x is greater equal to 0. As 1/x to be defined , precisely x greater than 0. Now squaring both side of the equation and multiplying both side by x followed by rearrangement gives x^3 - x^2 - x + 2 = 2×(x^3 - x^2 - x + 1)^1/2 Which leads to x^2 - x - 1 = 0 So x may be (1+√5)/2 or (1-√5)/2 But positive value is the only acceptable value here. Again checking the uniqueness of the solution it gets to be unique. So x= (1+√5)/2

Another solution would be a geometric analysis. Think (x-1 / x) ^ (1/2) = a and (1-1 / x) ^ (1/2) = b, it is easy to see that it is possible to form two triangles whose heights are equal, hence we show that there is a right triangle formed by the other two triangles. Then use the Pythagorean theorem.

Carlos Baião - 2 years, 2 months ago

Log in to reply

Interesting thinking.

Arka Dutta - 2 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...